Comprehensive chemical characterization study of three major fruit residues from São Paulo State (Brazil): banana pseudostem, orange bagasse, and guava seed cake - Vieira, Rogerio Martins [UNESP]; Gonçalves, Adilson Roberto [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2024)
Chemical characterization is a crucial step and decision tool before any application of fruit crop residues. This study aims to evaluate the applicability of traditional chemical characterization methods for banana pseudostem, guava seed, and orange bagasse. An analysis of extractives removal time and sugar solubilization during this process was performed. The residues were evaluated based on the cellulose, hemicellulose, lignin, extractives, and ash contents, in addition to the holocellulose and α-cellulose fractions, followed by FTIR spectroscopy. Acid-soluble lignin was evaluated by UV–visible spectrophotometry with different extinction coefficients and wavelengths. The results showed that extractives’ removal for 4 h was sufficient for all materials, and a varied composition was observed among the biomasses. The guava seed had the highest lignin content, 41.66%, banana pseudostem had 33.97% cellulose, and orange bagasse had a high extractive content, 60.78%. The mass balance for all biomasses was above 92%, which suggests the applicability of such chemical characterization methods for fruit residues. A significant influence of different parameters in the determination of soluble lignin was observed. Thus, the present study serves as a basis for future research on the use and application of fruit residues, since there are no specific and complete studies on its characterization; including the evaluation of a greater number of plant varieties to obtain more representative results.
Keywords: Bioenergy; Biorefinery; Chemical characterization; Lignocellulosic biomass